2022
DOI: 10.1002/lol2.10255
|View full text |Cite
|
Sign up to set email alerts
|

Changes in phytoplankton and biomineral content of particles during episodic fluxes to abyssal depth

Abstract: Large episodic pulses of particulate organic carbon (POC) at the deep‐sea (~ 4000 m) time‐series Sta. M in the Northeast Pacific Ocean have increased in frequency and magnitude over the past 32 years. We inferred the ecological drivers of these events by quantifying the phytoplankton and biomineral composition within particles collected by bottom‐moored sediment traps immediately before, during, and after 14 high‐flux events. Samples collected during high‐flux events contained a significantly different phytopl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…This represents an important advance in our understanding of marine arsenic biogeochemistry. Through microscopic and chemical analyses of sinking particles, Michaud et al (2022) linked the ocean surface to its abyssal depths to understand the origins of large, heretofore unexplained, episodic pulses of organic carbon (OC). By quantifying phytoplankton presence and biomineral composition, their measurements suggested that these high‐flux events stem from the transport of coastal diatom blooms that have been greatly transformed by pelagic food webs en route to the deep ocean, thus improving our understanding of high OC flux events.…”
mentioning
confidence: 99%
“…This represents an important advance in our understanding of marine arsenic biogeochemistry. Through microscopic and chemical analyses of sinking particles, Michaud et al (2022) linked the ocean surface to its abyssal depths to understand the origins of large, heretofore unexplained, episodic pulses of organic carbon (OC). By quantifying phytoplankton presence and biomineral composition, their measurements suggested that these high‐flux events stem from the transport of coastal diatom blooms that have been greatly transformed by pelagic food webs en route to the deep ocean, thus improving our understanding of high OC flux events.…”
mentioning
confidence: 99%